The Effects of Gross Regional Domestic Product and Regional Expenditure on Local Revenue with Unemployment Moderation - Wendelina Paulina Faubun; Elsyan R. Marlissa; Transna Putra Urip (International Journal of Accounting and Management Information Systems, 2026)
Purpose: This study examines the effect of Gross Regional Domestic Product (GRDP) and regional expenditure on local own-source revenue (PAD) in Pegunungan Bintang Regency over the 2010-2024 period, and tests whether the Open Unemployment Rate or localy Tingkat Pengangguran Terbuka (TPT) moderates these relationships. Research Methodology: Using annual secondary time-series data spanning fifteen years, obtained from regional budget realization reports and the Central Statistics Agency, the study applied multiple linear regression and moderated regression analysis, estimated in SPSS after classical assumption testing, with the type of moderation classified following Baron and Kenny's criteria. Results: GRDP and regional expenditure each had a positive and significant effect on local own-source revenue, and the open unemployment rate itself had a significant effect on revenue. The interaction terms confirmed that the unemployment rate significantly moderates both relationships, in each case as a quasi, or partial, moderator, since the direct effects of GRDP and regional expenditure remained significant even after the interaction terms were introduced. Conclusions: Economic growth and regional spending both feed into local revenue capacity in Pegunungan Bintang Regency, but the strength of that conversion depends on labor market conditions. Limitations: The single-region, time-series design and the two-variable model restrict how far the findings can be generalized. Contributions: The study extends fiscal federalism and labor market theory to a remote, mountainous Papuan regency and offers a moderation-based account of local revenue determinants rarely tested in this setting.